Analysis of the Factors Influencing the Decreasing Profit in Ayam Penyet Restaurant, Surabaya, Medan - Rini Handriani; Suriana Suriana; Widia Wardani (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine whether the marketing mix strategy, demand volume, raw material costs and bad debts have a significant effect on decreasing profits at Ayam Penyet Restaurant Surabaya Medan both partially and simultaneously and how big the effect is. The method used in this study is a quantitative method with several tests, namely reliability analysis, classical assumption deviation test and linear regression. Based on the regression results of the primary data processed using SPSS 20, the multiple linear regression equation is obtained as follows: Y = -1.881 + 0.412 X1 + 0.214 X2 + 0.291 X3 + 0.162 X4 + e. Partially, the marketing mix strategy variable (X1) has a significant effect on profit reduction, as evidenced by the t count > t table (4.883 > 1.988). The demand volume variable (X2) has a significant effect on profit reduction, as evidenced by the t count > t table (2.233 > 1.988). The raw material cost variable (X3) has a significant effect on profit reduction, as evidenced by the t count > t table (3.288 > 1.988). The bad debts variable (X4) has a significant effect on profit reduction, as evidenced by the t count > t table (2.298 > 1.988). Simultaneously, marketing mix strategy variables (X1), demand volume (X2), raw material costs (X3), and bad debts (X4) have a significant influence on profit decline. This means that the hypothesis in this study is accepted, as evidenced by the calculated F value > F table (49.824 > 2.48). Marketing mix strategy variables (X1), demand volume (X2), raw material costs (X3), and uncollectible accounts (X4) are able to contribute to the variable effect of decreasing profits by 68.7% while the remaining 31.3% is influenced by other variables not examined in this study. From the conclusions above, the authors suggest that the leadership should pay more attention to the demand volume which is good enough so that the sales process remains stable in the long run. Companies should put more pressure on outlets that have uncollectible accounts so that the financial process can return to stability. Employees should continue to work with good performance according to company regulations. the author suggests that the leadership should pay more attention to the demand volume which is good enough so that the sales process remains stable in the long term. Companies should put more pressure on outlets that have uncollectible